2012
DOI: 10.1073/pnas.1205902109
|View full text |Cite
|
Sign up to set email alerts
|

Detecting activity-evoked pH changes in human brain

Abstract: Localized pH changes have been suggested to occur in the brain during normal function. However, the existence of such pH changes has also been questioned. Lack of methods for noninvasively measuring pH with high spatial and temporal resolution has limited insight into this issue. Here we report that a magnetic resonance imaging (MRI) strategy, T 1 relaxation in the rotating frame (T 1 ρ), is sufficiently sensitive to detect widespread pH changes in the mouse and human brain evoked by systemically manipulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
173
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(186 citation statements)
references
References 26 publications
10
173
3
Order By: Relevance
“…The present findings suggest that this pH-normalizing effect of reperfusion may explain, in part, why superoxide production is greater in reperfused than nonreperfused ischemic brain, and why both NOX2 inhibitors and NMDA receptor antagonists are better neuroprotective agents in reperfused brain than nonreperfused brain (41)(42)(43). The degree of intracellular acidification shown here to influence neuronal superoxide production is within the range induced by physiological brain activity (28,44). Intracellular pH changes may thereby also influence the normal, physiological intercellular signaling mediated by neuronal superoxide production (45).…”
Section: +mentioning
confidence: 61%
“…The present findings suggest that this pH-normalizing effect of reperfusion may explain, in part, why superoxide production is greater in reperfused than nonreperfused ischemic brain, and why both NOX2 inhibitors and NMDA receptor antagonists are better neuroprotective agents in reperfused brain than nonreperfused brain (41)(42)(43). The degree of intracellular acidification shown here to influence neuronal superoxide production is within the range induced by physiological brain activity (28,44). Intracellular pH changes may thereby also influence the normal, physiological intercellular signaling mediated by neuronal superoxide production (45).…”
Section: +mentioning
confidence: 61%
“…While pH affects neural activity, neural activity causes pH alterations that vary in location and time (Chen and Chesler, 1992;Dulla et al, 2005;Makani and Chesler, 2007). Local pH changes occur in the brain during normal function (Chesler and Kaila, 1992;Magnotta et al, 2012), and neuronal firing causes both intracellular and extracellular pH shifts (Chesler, 2003;Chesler and Kaila, 1992;Kim and Trussell, 2009;Trapp et al, 1996). Rapid changes in intracellular pH have been observed at Drosophila nerve terminals during high-frequency in vivo activity (Caldwell et al, 2013;Rossano et al, 2013), while in the mammalian CNS, intense and synchronous activity of neural networks is accompanied by an initial alkalinization followed by a slower wave of acidification of the extracellular environment (DeVries, 2001;Du et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative fMRI approach to BOLD was recently proposed based on T1 relaxation in the rotating frame (T1ρ), called functional T1 ρ mapping (fT1ρ) (Jin & Kim, 2013; Johnson, Heo, Thedens, Wemmie, & Magnotta, 2014; Magnotta et al., 2012). This technique aims to quantitatively map the spin‐lock–based T1ρ relaxation time temporally and is sensitive to chemical exchange of protons between water and amide, hydroxyl, and/or amine groups (Jin, Autio, Obata, & Kim, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that both BOLD and fT1ρ signals reflect functional activity in vivo (Hulvershorn et al., 2005; Jin & Kim, 2013; Magnotta et al., 2012), however, it remains unclear how these two imaging methods relate to each other (Magnotta et al., 2014). In this exploratory study, we investigated the relationship between BOLD and fT1ρ activation in response to a flashing checkerboard stimulus in participants with bipolar disorder and in matched healthy controls.…”
Section: Introductionmentioning
confidence: 99%